Identification and Mapping of the Clubroot Resistance Gene CRd in Chinese Cabbage (Brassica rapa ssp. pekinensis) - Pang, Wenxing; Fu, Pengyu; Li, Xiaonan; Zhan, Zongxiang; Yu, Sha; Piao, Zhongyun (Frontiers in Plant Science, 2018)
The rapid spread of clubroot disease, which is caused by Plasmodiophora brassicae, threatens Brassicaceae crop production worldwide. Breeding plants that have broad-spectrum disease resistance is one of the best ways to prevent clubroot. In the present study, eight Chinese cabbage germplasm were screened using published CR loci-/gene linked markers. A clubroot resistant gene Crr3 potential carrier ‘85-74’ was detected which linked to marker BRSTS61, however, ‘85-74’ shows different responses to local pathogens ‘LAB-19’, ‘LNND-2’, and ‘LAB-10’ from ‘CR-73’ which harbors Crr3. we used a next-generation sequencing-based bulked segregant analysis approach combined with genetic mapping to detect clubroot resistance (CR) genes in an F2 segregant population generated from a cross between the Chinese cabbage inbred lines ‘85-74’ (clubroot resistant) and ‘BJN3-1’ (clubroot susceptible). The ‘85-74’ line showed resistance to a local pathogen ‘LAB-19’ which was identified as race 4; a genetic analysis revealed that the resistance was conferred by a single dominant gene. The clubroot resistance gene which we named CRd was mapped to a 60 kb (1 cM) region between markers yau389 and yau376 on chromosome A03. CRd is located upstream of Crr3 was confirmed based on the physical positions of Crr3 linked markers. The identification of CRd linked markers can be applied to marker-assisted selection in the breeding of new CR cultivars of Chinese cabbage and other Brassica crops.